Math engagement among secondary school students personality factors as facilitators and inhibitors - Adriano, Anna Celeste B. (College of Education, University of the Philippines Diliman, 2020)
Previous studies have investigated the learning conditions that affect students' engagement in math. This study sought to explore math engagement from the perspective of students. It aimed to find out if personality factors (i.e. neuroticism, extroversion) of students influenced math engagement. To find out if personality factors were related to math engagement, a mixed design was employed. A survey was conducted using the Eysenck Personality Inventory (EPI) and Student Engagement for Math Classrooms Scale (SEMCS) on 420 secondary students from Metro Manila. The results showed that high levels of neuroticism and extroversion were associated with Math engagement. Through focus group discussions, this study also uncovered how personality factors manifested in classrooms as students approached and performed in a math challenge. Findings revealed that students faced and processed challenges differently in the same learning conditions. And in order to offer a more engaging and fulfilling learning experience for the students, personality factors are encouraged to be considered in teaching plans and strategies.